Examining Chemical and Sensory Differences of New American Aroma Hops Grown in the Willamette Valley, Oregon. (6th October 2022) - Van Simaeys, Karli R.; Féchir, Michael; Gallagher, Andy; Stokholm, Arnbjørn; Weaver, Garrett; Shellhammer, Thomas H.
Abstract: The influence of growing region on hop quality is examined in three American aroma hop varieties (Mosaic®, Simcoe® and Strata®) from eleven locations throughout the Willamette Valley, OR. Hops from each site were analyzed for total oil content, α- and β-acids, and the oil was analyzed via GC-FID to quantify selected aroma compounds. Single-field IPAs were brewed using composite samples from each field and assessed via sensory evaluation. While hop variety had the largest influence on chemical differences, as expected, Analysis of Variance revealed differences between fields within the same variety. Sensory discrimination and descriptive testing of the single-field IPAs also showed significant region-based differences among samples within the same variety. Supplemental data for this article is available online at